Some Evidence on the Effect of Company Size on the Cost of Equity Capital - Alberts, W. W.; Archer, S. H. (Journal of Financial and Quantitative Analysis, 1973)
The objective of this paper is to carry out tests of the general hypothesis, most recently urged by Scherer [14, pp. 100–102] and Weston and Brigham [17, p. 689], that the cost-of-equity capital of small industrial corporations is greater than that of large industrial corporations. The paper denotes this cost as ke and defines it as the expected rate of return on the stock of a company when the current price of the stock is in equilibrium. A common designation of ke of course is the equity capitalization rate. It will be noted that this definition of the cost-of-equity capital abstracts from the flotation costs that are usually incurred when companies sell new stock. Archer and Faerber [2] have already shown that these costs are inversely related to the size of companies.